På spaning efter den gräns som flytt. Gränsbegrepp i modern svensk poesi baserande på dikter av Katarina Frostenson och Stig Laarsson - Niewiarowska-Rasmussen, Ewa (Folia Scandinavica Posnaniensia, 2017)
The word „limit" has become one of the keywords of modern Swedish poetry, in which it is connected with different poetic determinants. An analysis of the poetry of Katarina Frostenson and Stig Larsson leads to the conclusion that in this age of deconstruction, inter-textuality and postmodemism, among other new literary phenomena, poetry as art has lost its traditional limits. The modern Swedish poets aim at achieving absolute freedom of poetic language, now separated from the outside, non-literary world. They try to prove that meaning is no longer explicitely defined. The poetry of Katarina Frostenson and Stig Larsson attempts to abolish the separation between the persona of the speaker and the world, between the subject and the object.